Fantastic Lifestyle Questionnaire applied to undergraduate medical students during the COVID-19 pandemic: a factor analysis - Martins, João Mateus Silva; Ferreira, Esther Angélica Luiz; Valete, Cristina Ortiz Sobrinho; Gramasco, Hendrick Henrique Fernandes [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: To identify what structure represents life style in medical students, in a public university, with the application of the Fantastic Lifestyle Questionnaire. METHODS: This is a cross-sectional exploratory study. The Fantastic Lifestyle Questionnaire was applied online to medical students. Factorial analysis was realized and factors were extracted by principal components method. Rotation was conducted by Varimax method. RESULTS: Sixty-one questionnaires were analyzed. Students were male in 45.9%, single in 88.5%. The model was composed of three factors that explained 63.5% of all observed variance. The factors related to sleep perception, nutrition and stress, followed by relationships and entertainment and then, activity. Cronbach’s alpha was 0.81, which was considered good. CONCLUSION: The model composed by the three factors observed in this group of students represented the construct quality of life, evaluated by the Fantastic Lifestyle Questionnaire. This result may provide substrate to actions that aim to improve quality of life and well-being in medical students from this university.
Keywords: COVID-19; Factor analysis; Lifestyle; Medical students; Quality of life